EMOTIONAL METAPHORS IN RUSSIAN AND UZBEK LANGUAGES: COGNITIVE AND CULTURAL ANALYSIS - Kodirova Zebiniso Abdigaffarovna; Atavullaeva Saida Jumabekmuradovna (Western European Studies, 2025)
Metaphors serve as a powerful linguistic mechanism in shaping human perception and expressing inner emotional states. Emotional metaphors, in particular, play a pivotal role in conveying psychological experiences through culturally embedded imagery. This study investigates the conceptualization of emotions through metaphors in Russian and Uzbek languages by focusing on their cognitive and linguocultural dimensions. Based on a corpus of 600 metaphorical expressions (300 from each language), this research categorizes and analyzes metaphors related to anger, love, fear, and joy. The study reveals that while Russian emotional metaphors are often grounded in bodily sensations and psychological intensity, Uzbek emotional metaphors tend to draw from spiritual, natural, and religious imagery. Comparative results highlight both universal cognitive models and culturally specific metaphorical frameworks in the expression of emotions.
Keywords: emotional metaphors; cognitive linguistics